PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TIME TOKEN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN TERMOKIMIA DI KELAS XI IPA SMAN 2 PEKANBARU - Bismi Hayati Hayati; Johni Azmi Azmi; Rasmiwetti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research is about applying type cooperative learning model Time Token. It was done to know the increase student achievementon the subject termokimia in class XI IPA SMAN 2 Pekanbaru. The type of this research is experimental research with pretest-postest design. The sample consists of two classes. They are class XI Science 2 as an experimental class and class XI Science 3 as a control class which were decided randomly after doing normality and homogenity test. Experimental class is a class that is applied cooperative learning model Time Token, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 1,82>1,66, means that the application of cooperative learning model Time Token can improve student achievement on the subject of termokimia class XI IPA SMAN 2 Pekanbaru, increase learning of 5,07%. Keywords: cooperative learning, Time Token